PM2.5 Simulations for the Seoul Metropolitan Area: (VI) Estimating Influence of Sectoral Emissions from Chungcheongnam-do 수도권 초미세먼지 농도모사: (VI) 충남 배출 부문별 영향 추정 - Kim, Eunhye; Kim, Hyun Cheol; Kim, Byeong Uk; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2019)
We investigate the impact of Chungcheongnam-do (CCND) sectoral emissions to PM2.5 concentrations in the Seoul Metropolitan Area (SMA), South Korea. As major suppliers of the SMA’s power, CCND’s energy generation units are known for important emissions sources to affect SMA air quality, however, the influences of other emission sectors in CCND are not fully addressed. Impacts from seven major emissions sectors (i.e. energy combustion, industrial combustion, industrial process, nonroad, on-road, fugitive, and bio-combustion) in CCND are separated using a brute force method with Community Multi-scale Air Quality simulations for the year of 2015. Simulations suggest that seven major emission sectors in CCND contribute 1.74 μg/m3 (6.6%) of annual SMA PM2.5 concentrations, 26.42 μg/m3, with clear seasonal variation from meteorological effect. While three sectors, industrial combustion, industrial process, and energy combustion, are the most dominant contributors, the impacts from industrial combustion (0.93 μg/m3, 3.5%) and industrial process (0.36 μg/m3, 1.4%) are larger than that of energy combustion (0.23 μg/m3, 0.9%). We conclude that, in order to improve SMA air quality, collaborative control of emissions both from SMA and neighboring administrative region, as well as an additional focus on emissions from non-energy sectors are required
Keywords: Impact; Particulate matter; Region-wide; Sectoral emissions